2022
DOI: 10.1038/s41598-022-12844-8
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability comparison between young males after 4–6 weeks from the end of SARS-CoV-2 infection and controls

Abstract: Due to the prolonged inflammatory process induced by infection of the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), indices of autonomic nervous system dysfunction may persist long after viral shedding. Previous studies showed significant changes in HRV parameters in severe (including fatal) infection of SARS-CoV-2. However, few studies have comprehensively examined HRV in individuals who previously presented as asymptomatic or mildly symptomatic cases of COVID-19. In this study, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…Lastly, decreased SD2 and increased DFA2 from the nonlinear analyses in our study indicate a more ordered (i.e., less random) pattern in beat-to-beat intervals (Shaffer & Ginsberg, 2017). This observed reduction in the complexity within the time-series was also noted in a previous case-control study, though with different nonlinear metrics (Solinski et al, 2022), and may be interpreted as another finding potentially indicative of ANS dysfunction in COVID-19 survivors. Even where significant between-group differences in our study were not observed, it is interesting to consider the COVID survivors' HRV data in relation to normative values and to the CON cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Lastly, decreased SD2 and increased DFA2 from the nonlinear analyses in our study indicate a more ordered (i.e., less random) pattern in beat-to-beat intervals (Shaffer & Ginsberg, 2017). This observed reduction in the complexity within the time-series was also noted in a previous case-control study, though with different nonlinear metrics (Solinski et al, 2022), and may be interpreted as another finding potentially indicative of ANS dysfunction in COVID-19 survivors. Even where significant between-group differences in our study were not observed, it is interesting to consider the COVID survivors' HRV data in relation to normative values and to the CON cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies show that an elevated sympathetic drive can impede the FMD response (Hijmering et al, 2002; Thijssen et al, 2006). Likewise, a lower heart‐rate‐variability in individuals with a SARS‐CoV‐2 infection, but displaying mild symptoms, compared with healthy, control counterparts (Kurtoglu et al, 2022; Solinski et al, 2022). Furthermore, persistent sympathetic overactivation (66% higher MSNA) along with blunted vascular function (45% lower FMD) have been observed cross‐sectionally among older adults who were hospitalized with COVID‐19 and were studied 1 year after infection compared to well‐matched control subjects (Faria et al, 2022), further suggesting long‐lasting autonomic dysfunction among those previously infected with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide evidence in favor of the dysautonomia hypothesis, we investigated heart rate variability (HRV) in both the time and frequency domains by performing a non-invasive study of sympathetic and parasympathetic activity in long COVID-19 patients. HRV [31][32][33][34][35] is a legitimate dysautonomia diagnosis. It is possible that HRV may be a useful tool for examining the neuroimmune systems and inflammatory processes of long COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%